Metagenomic analysis reveals the novel role of vaginal Lactobacillus iners in Chinese healthy pregnant women - Xudong Wang; Qingru Jiang; Xiaohui Tian; Wei Chen; Junrui Mai; Gan Lin; Yingfang Huo; Haiyang Zheng; Dandan Yan; Xiaohong Wang; Tian Li; Yu Gao; et al. (npj Biofilms and Microbiomes)
Abstract This study investigated the relationship between vaginal microbiota and women’s health conditions in 95 Chinese pregnant women in their third trimester. We conducted vaginal metagenomic analysis, examining species, functional pathways, and genes, and utilized correlation and LEfSe analyses to link microbiota to health conditions. Results revealed that healthy participants exhibited higher levels of Lactobacillus iners, with its abundance associated with tetrahydrofolate biosynthesis pathways. They also possessed more glycosyltransferase and ErmB antibiotic resistance genes compared to women with diagnosed conditions. Comparative genomics demonstrated that L. iners strains linked to bacterial vaginosis (BV) possessed more genes encoding biofilm-associated YhgE/Pip domain-containing proteins than healthy-associated strains. Notably, three BV-associated L. iners strains exhibited stronger biofilm formation abilities than four healthy-associated strains isolated in this study. Also, four out of seven L. iners strains inhibited the growth of Gardnerella vaginalis. Overall, L. iners may help maintain vaginal ecosystem stability in Chinese pregnant women.